Manipulation with cultural memory as an unplanned result of management of social technologies in knowledge society - M. V. Melik-Gaykazyan (Высшее образование в России)
Basing on the studies of semiotic mechanisms of management conducted in the context of information-synergetic approach and basing on the conception of memory-turn the article clarifiesthe unplanned result of management in a sphere of social technologies – manipulation withcultural memory. The obtained result was supported by the RFBR (the project № 10-06-00313).